Not Guilty, but Guilty: Race, Rumour, and Respectability in the 1882 Abortion Trial of Letitia Munson - Beausaert, Rebecca (Ontario History)

(untitled) (The Ontario Historical Society, 2014)
In 1882, an accused, elderly African-Canadian woman—a former slave and known midwife, healer, and abortionist in the town of Woodstock, Ontario—was implicated in the death of a younger White woman, allegedly from a botched abortion. The article focuses on the ways the accused was viewed by the local media, specifically references to her race, age, and “suspect” knowledge of medical practices. Tried in a court of law and found not guilty, the press nevertheless declared themselves “morally certain” of her guilt and attempted to sway public opinion in a way that brought race to the forefront. The trial and its aftermath raise a number of important questions regarding socially-constructed configurations of race, gender, justice, rumour, and respectability in a nineteenth-century Ontario town chiefly populated by Anglo-Celtic Protestants.